Very Low Levels of Microscopic Hematuria in Potential Living Kidney Donors Is Associated with Pathology That Precludes Donation. (July 2018) - Kumar, Vineeta; Saha, Manish; Hanaway, Michael; Locke, Jayme; Julian, Bruce; Gaston, Robert
Abstract : Background: A threshold of ≥3 rbc/hpf (red blood cells/high power field) or higher prompts additional testing when evaluating potential living kidney donors at most centers in the United States. In our experience, a lower degree of hematuria has yielded pathology that precluded kidney donation and here in we present the results of a single center experience. Methods: We prospectively identified isolated asymptomatic microscopic hematuria in 19 out of 1124 potential living kidney donors. Microscopic hematuria was defined as presence of ≥1 rbc/hpf and persistent by presence on ≥2 separate urinalysis. Isolated was defined as presence of microscopic hematuria and with preserved GFR, absence of proteinuria, microalbuminuria or hypertension and no identifiable anatomical cause on native kidney imaging. Donors expressing continued interest had an evaluation with a cystoscopy. If unrevealing, they underwent a native kidney biopsy analyzed by a single pathologist using light, immunofluorescence and electron microscopy. Results: There were no biopsy related complications. Degree of hematuria was modest ranging from 0-2 upto 3-10 rbc/hpf. Higher degree of hematuria was not isolated. 3/19 had IgA nephropathy and were not approved for kidney donation. All of these donors were related to their recipients. 1/19 had arteriosclerosis. Thin basement membrane disease (GBM) diagnosed after ruling out Alports was the most common finding in 11/19 patients and 4/19 had possible thin GBM based on segemental thinning only. These 15/19 were given a choice to donate after extensive counseling. One and two year follow up data have no worsening of hematuria or any of the renal parameters since donation. Conclusion: Persistent asymptomatic microscopic hematuria of very minor degree in potential kidney donors with a biologically related recipient can be associated with pathologic findings that preclude kidney donation. A higher threshold of rbc/hpf on urine analysis as currently used can lead to a missed diagnosis and alter long term prognosis. At our center we have lowered our definition to ≥1 rbc/hpf after the results of this analysis.